Kecerdasan Emosi Sosial Kemahiran Penyesuaian Diri Dalam Kalangan Pelajar SekolahMenengah (The Social Emotional Intelligence Of Adaptability Skills Among Secondary School Students) - Lailawati Madlan Endalan; Abdul Adib Asnawi; Chua Bee Seok; Ferlis Bullare @ Bahari; Jasmine Adela Mutang; Rosnah Ismail (2018)
Social emotional intelligence, a combination between emotion and social intelligence, is a very important aspect of one's self. It is divided into five components which is intrapersonal, interpersonal, stress management, adaptation and general mood. Social emotional intelligence directly affects the behavior, emotion and decision making of an individual. Secondary school students are a group of early teenager and still in the process of identity formation. Therefore, it is important to know the social emotional intelligence of adaptability skills especially among school students as it has long-term impact on their performance. The main objective of this study is to examine the social emotional intelligence scores among high school students in Kota Kinabalu, Sabah. The sample in this study consisted of Form One to Form Six students from various schools around Kota Kinabalu. A set of questionnaire used in this study is The Emotional Quotient Inventory Youth Version (EQ-i: YV) designed by Bar-On and Parker (2000) contains 60 questions with four likert scale. The data obtained were analyzed using the IBM SPSS version 24.0. The results of this study showed that the social emotional intelligence as a whole is at a moderate level. Meanwhile, there are differences in adaptability skills between male and female students, where the mean score for male students is higher than female students. As for the implication, related parties such as ministries of education, parents and the community can obtain relevant information for the purpose of implementation of programs and activities to enhance emotional intelligence and adaptability skills that are appropriate to the current generation Z.